Stress-Strain State of a Physically Non-Linear Three-Layer Rectangular Plate with a Compressed Filler - Denis V. Leonenko; Anastasiya S. Zelenaya (Механика машин, механизмов и материалов, 2018)
The stress-strain state of physically nonlinear asymmetric three-layer rectangular plates with a compressed filler was studied. For outer layers Kirchhoff’s hypotheses are accepted, the deformed normal remains rectilinear in a rigid compressible filler. Ilyushin’s “elastic” solutions method was used while solving the issue. Numerical results for a three-layer metal-polymer plate are presented.